2020
DOI: 10.5194/os-2020-50
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beaching patterns of plastic debris along the Indian Ocean rim

Abstract: Abstract. A large percentage of global ocean plastic waste enters the northern hemisphere Indian Ocean (NIO). Despite this, it is unclear what happens to buoyant plastics in the NIO. Because the subtropics in the NIO is blocked by landmass, there is no subtropical gyre and no associated subtropical garbage patch in this region. We therefore hypothesise that plastics "beach" and end up on coastlines along the Indian Ocean rim. In this paper, we determine the influence of beaching plastics by applying different … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…As expected, B surface particles intercepting Cabo Verde are more likely to pass through the highly productive (e.g., Mittelstaedt, 1991;Van Camp et al, 1991;Lathuilière et al, 2008) areas of intensive fishing activity along the northwest African coast, extending from the Canaries to the Mauritanian coast (Figure 7D). Indeed, Fernandes (2019) found that >60% (by mass) of the plastic debris collected in the northern side of Santa Luzia island in Cabo Verde were fishing gear.…”
Section: Marine-based Sourcessupporting
confidence: 69%
See 2 more Smart Citations
“…As expected, B surface particles intercepting Cabo Verde are more likely to pass through the highly productive (e.g., Mittelstaedt, 1991;Van Camp et al, 1991;Lathuilière et al, 2008) areas of intensive fishing activity along the northwest African coast, extending from the Canaries to the Mauritanian coast (Figure 7D). Indeed, Fernandes (2019) found that >60% (by mass) of the plastic debris collected in the northern side of Santa Luzia island in Cabo Verde were fishing gear.…”
Section: Marine-based Sourcessupporting
confidence: 69%
“…Driven by the relaxation of the trade winds and consequent intensification of the North Equatorial Counter Current, the Mauritanian Current reaches its northernmost extension (20 • N) during summer and autumn, where it intersects the North Equatorial Current and turns southwestward in the direction of Cabo Verde. During winter and spring the opposite occurs, as the trade winds intensify and force the Canary Current upwelling system to reach its southernmost extension (15 • N, Mittelstaedt, 1991;Van Camp et al, 1991). Such dynamic variability at the Mauritania coast is expected to affect the Cabo Verde islands, located 450-600 km west.…”
Section: Oceanographic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Martinez-Ribes et al, 2007;Turrell, 2020a). Elsewhere, however, particularly in the case of remote islands with minimal or no population, debris accumulating on the coast may have been transported over great distances by ocean currents, winds, and waves (van Sebille et al, 2020). These islands, many of which belong to small island developing states, are faced with the deeply inequitable situation of bearing the costs of removing waste they were not responsible for generating, contrary to the "polluter pays" principle (OECD, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…assuming knowledge of some input distribution of marine debris and predicting where that debris is transported (e.g. Kaandorp et al, 2020;van der Mheen et al, 2020;Chassignet et al, 2021), or backward-in-time, i.e. simulating trajectories that lead to a site of interest and inferring debris sources based on where debris passed through in the past (e.g.…”
Section: Introductionmentioning
confidence: 99%